Kedudukan dan Perlindungan Saksi Mahkota dalam Tindak Pidana Pencurian dengan Kekerasan (Studi Kasus Pengadilan Negeri Denpasar) - Ni Made Elly Pradnya Suari; I Made Minggu Widyantara; Ni Made Sukaryati Karma (Jurnal Interpretasi Hukum, 2020)
The presence of witnesses in the evidence is the keyword in disclosing the facts of criminal cases. The crown witness is often present at court. However, there are many differences of opinion in the Jurisprudence regarding the use of crown witnesses in court because there is no legal regulation that explicitly regulates the use of crown witnesses in criminal justice. Based on these problems, this study described how the protection of the rights of defendants as crown witnesses in criminal acts of theft with violence and how the position of crown witnesses in criminal acts of theft with violence. This research was designed using a normative legal research method and a conceptual approach. In the Criminal Procedure Code, there is no prohibition for a defendant to provide information for other defendants as far as using a splitsing system so that defendants who are crown witnesses still receive legal protection. The decision of the Supreme Court Number 1942 K / PID / 2012 which in its verification process used a crown witness. In this case, the public prosecutor presented the crown witness due to the lack of evidence especially witness testimony evidence. The role of the crown witness is very important to uncover criminal events because the defendant knows, sees, and commits criminal theft with violence. The result of this study showed that the protection of the rights of the defendant as a crown witness is equated with the rights of the defendant in general, which is regulated in Article 50 to Article 68 of the Criminal Procedure Code and witness rights set out in Article 5 of Law Number 31 of 2014. The position of the crown witness is justified in proof-based on the Circular Attorney General's Office of the Republic of Indonesia Number B-69 / E / 02/1997 of 1997 concerning Proof Law in Criminal Cases.